EVALUASI PELAKSANAAN PROGRAM BERAS MISKIN DI DESA TONANG KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Eliezer E.42009056 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This script intend to evaluate the rice for poor implementation program at Tonang Village, tittle of the script raised by the issues of implementation rice for poor program at Tonang Village that still can’t goes well. This script uses a qualitative research method by using three stages: phase 1. Find problems and phase 2. define problems, formulate and phase 3. concluded last issue. Research sites at Tonang Village. The subject of this research is villahe government, district government and society that accept the ‘rice for poor’.The conclusion of this script is the lack of implementation effectivity rice for poor program becauce inadequate infrastructure, ineffective supervision and communication that have not been well established between the government and the society. Therefore, the government should fix the infrastructure, improve supervision and establish good communication with the society . Keywords : Evaluation, Rice for poor, Communication and Resources